Teachers Strategies in Teaching English to Young Learners in Private Primary Schools in Yogyakarta - Sarly Gustini Pratiwi; Nur Fatimah; Nur Rifai Akhsan (Ahmad Dahlan Journal of English Studies, 2021)
Teaching English to young learners is not easy, because English is not the mother tongue and it makes children difficult to master English well. Strategies are needed when teaching it. For that reason, the researchers conducted this study to describe the problems faced by the teachers in teaching English to young learners and to explain their strategies in teaching English to private primary schools students. This research was conducted by using descriptive qualitative research. The data were collected through semi-structured interviews with teachers at private primary schools in Yogyakarta. The subjects of the research involved six English teachers in the even semester of the academic year 2019/2020 at the private primary schools in Yogyakarta. To get the validity of the data, the triangulation of data sources with the same technique, namely interview was used, and the result of this research was checked by the research subjects to ensure the data are valid. In this study, the researchers analyzed the data, categorizing the data, making explanations, and finally drawing conclusions. The result of this research indicated that there are nine problems faced by the teacher when teaching English to young learners. They are limited time, diverse characters of students, less focused students, bickering students, the English position in the national curriculum, a large number of students and classes, unsupported facilities, learning media, and the fact that English is not a tool of communication. Every teacher has his or her strategies when teaching English to young learners, the strategies are cooperative, contextual, think together with the students, expository, inquiry, exploration-elaboration-collaboration, TPR, students active learning, and using video strategies